Exploring the perspectives of healthcare workers and Program managers on the use of Truenat as a new tool for TB and DR-TB diagnosis in Nigeria: A qualitative study. - Nkiru Nwokoye; Austin Ihesie; Jamiu Olabamiji; Kingsley Ochei; Rupert Eneogu; Michael Umoren; Femi Odola; Debby Nongo; Aderonke Agbaje; Bethrand Odume; Omosalewa Oyelaran; Wayne van Germert; et al. (PLoS ONE)
Background World Health Organization in the year 2020 recommended the use of Truenat as a replacement for smear microscopy in Tuberculosis (TB) diagnosis and detection of rifampicin resistance. This study was designed to assess enablers and barriers to effective implementation of Truenat assays for TB diagnosis in Nigeria and determine the acceptability of use of Truenat among healthcare workers and TB Program managers in Nigeria. Methods A descriptive exploratory study design was used. Qualitative data were collected via Zoom platform using a pre-tested focus group discussion (FGD) guide and key informant interview (KII) guide. Four FGDs were conducted among Truenat laboratory staff, State Quality Assurance Officers, Local Government Tuberculosis Supervisors and Clinicians working at Truenat sites. Three KIIs were conducted among laboratory leads of Truenat implementing partners and the National TB Control Program. Results All the participants attested to the reliability and acceptability of Truenat results, they also highlighted the portability and ease-of-use especially for community outreach testing. Stakeholder engagement, training of Truenat laboratory staff and the perceived low operational cost associated with Truenat were the enablers of Truenat implementation. Major barriers to the implementation included human resource for health constraints, lack of power supply, frequent Trueprep breakdown and Truenat machine connectivity. The same human resource constraint was viewed as the major barrier to scale up of Truenat while employment and retention of Truenat staff coupled with training were seen as the facilitators to scale-up. The participants implored the manufacturers of Truenat to increase the number of modules for Truenat, enable the use of stool for diagnosis of TB and attach a solar panel to the machine. Conclusion Truenat has gained high acceptance among health workers and TB Program managers in Nigeria. The perceived low operational cost and low infrastructural requirements have been a major boost. There is a need to ensure the retention of health workers especially the Truenat laboratory staff. Training should be sustained including the payment of incentives. Increasing the number of modules of the Truenat machine, enabling the use of stool for TB diagnosis and having a solar panel attached to Truenat machine are essential.